Design Of Power Amplifier (Pa) Front-End Transmitter For Cdma Application At 900MHz Using 0.18 Micron Cmos Technology - Zahari, Muhamad Iskandar (Universiti Sains Malaysia, 2005)
Recent efforts in the design of integrated circuits for RF communication transceivers have focused on achieving higher levels of integration by including more and more analog functional blocks onto a single silicon CMOS chip. One of the final blocks that have yet to be successfully integrated is the power amplifier. The power amplifier is the final functional block in the transmit path and its function is to amplify the signal to be transmitted to the required transmit power level. In general, power amplifiers are difficult to integrate in CMOS because of technology limitations that severely limit the efficiency of the power amplifier. This thesis describes theoretical analysis and circuit techniques for the design and implementation of RF Class C power amplifier in CMOS technologies. There are very few methods exist for designing Class C power amplifier in the past, much of the design process has been empirical. The theoretical work in this thesis attempts to describe a method for designing a Class C power amplifier in CMOS without resorting to blind use of a circuit simulator. A 900MHz CMOS power amplifier was designed using Silterra 0.18µm RF MOSFET. This design is simulated using Cadence Design tool. In this simulation, the peak efficiency of the power amplifier was 37.7%. The power amplifier did meet the spectral mask requirements of CDMA (Code Division Multiple Access) cellular communications system for which it was designed. The power gain that had been achieved is 34.74 dB and meets the power amplifier specification for CDMA application.